(untitled) (Web of Teachers: Inderscience Research, 2024)
The era of global changes caused by social processes in the education system requires rapid development. Through education, a new generation is being formed in society, capable of fulfilling future tasks. PISA (The Program for International Student Assessment) is an international program for assessing student academic performance in the field of education, a test in which evaluates the knowledge and skills of schoolchildren in countries around the world in order to be able to put them into practice.